2019
DOI: 10.1371/journal.pone.0220466
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bonding strength between lithium disilicate ceramics and resin cement by multiple surface treatments after thermal cycling

Abstract: All-ceramic restoration has become a popular technology for dental restoration; however, the relative bond strength between the ceramic and resin limits its further application. Long-term high bond strength, especially after thermal cycling, is of great importance for effective restoration. The effect of physical and/or chemical surface treatments on bonding durability is seldom reported. To overcome this problem, we investigate the bond strength between lithium disilicate ceramics (LDC) and two kinds of resin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
3
10
0
Order By: Relevance
“…El-Damanhoury et al [40] concludes the better adhesion of LD ceramics to tooth structure facilitates the transmission of occlusal forces to pulp chamber walls. LD ceramics possess an excellent ability to resist damage induced by cyclic expansion and contraction from thermocycling due to combined outcomes of micromechanical and chemical bonding by the formation of Si-O-Si and -C-C-at the interface [41]. Higher fracture resistance of LD ceramic endocrowns observed in our study is also corroborated by GÜNGÖR et al [42].…”
Section: Discussionsupporting
confidence: 89%
“…El-Damanhoury et al [40] concludes the better adhesion of LD ceramics to tooth structure facilitates the transmission of occlusal forces to pulp chamber walls. LD ceramics possess an excellent ability to resist damage induced by cyclic expansion and contraction from thermocycling due to combined outcomes of micromechanical and chemical bonding by the formation of Si-O-Si and -C-C-at the interface [41]. Higher fracture resistance of LD ceramic endocrowns observed in our study is also corroborated by GÜNGÖR et al [42].…”
Section: Discussionsupporting
confidence: 89%
“…Futhermore, similar studies have tested various surface conditioning methods to different restorative materials ( 35 , 36 , 37 ). Li et al ( 35 ) investigated lithium disilicate ceramics with two resin cements after thermocycling and revealed that HF acid etching combined with a silane showed the highest SBS values. This study also point out that chemical bonding is more resistant to thermal damage than micromechanical interlocking.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the formation of an IPN in the novel silane coupling agent, which has a certain elasticity for resisting the internal stress caused by the different thermal expansion rates of ceramics and resins during TC. 40 It is noteworthy that the result exhibit significant differences compared to ANH and ANS (Groups 3 and 4). This result indicates that treatment with the bonding agent containing MDP has a positive effect on the bond durability.…”
Section: Discussionmentioning
confidence: 80%